2009
DOI: 10.1007/s11199-009-9666-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Role of Body Image Coping Strategies as Mediators or Moderators of the Links Between Self-Objectification, Body Shame, and Well-Being

Abstract: We examined self-objectification in relation to well-being, and the potential moderating versus mediating role of body image coping strategies (appearance fixing, avoidance, positive rational acceptance). Undergraduate women from southern Ontario, Canada (Sample 1, n=104; Sample 2, n=314) completed measures of depression, disordered eating attitudes, subjective well-being, and body-image coping. Self-objectification was related to greater depression, disordered eating attitudes, and lower subjective well-being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 46 publications
5
38
0
6
Order By: Relevance
“…The present research, in combination with other works (e.g., Choma et al 2007;Choma et al 2009;McKinley 1999;Mercurio and Landry 2008;Sinclair and Myers 2004), suggests that the negative effects of self-objectification extend to (less) positive psychological functioning. According to Keyes' notion of 'complete mental health' (Keyes 2005(Keyes , 2007, mental illness and mental health are related but distinct phenomenon that both need to be considered.…”
Section: Discussionsupporting
confidence: 82%
“…The present research, in combination with other works (e.g., Choma et al 2007;Choma et al 2009;McKinley 1999;Mercurio and Landry 2008;Sinclair and Myers 2004), suggests that the negative effects of self-objectification extend to (less) positive psychological functioning. According to Keyes' notion of 'complete mental health' (Keyes 2005(Keyes , 2007, mental illness and mental health are related but distinct phenomenon that both need to be considered.…”
Section: Discussionsupporting
confidence: 82%
“…Tačiau neigiamas ryšys tarp sudaiktinimo ir pasitenkinimo gyvenimu pasitvirtino. Tokio pobūdžio ryšys rastas ir ankstesniuose tyrimuose su studentėmis (Choma, Shove, Busseri, Sadava, Hosker, 2009;Mercurio et al, 2008). Mūsų atlikta analizė neleidžia atmesti galimybės, kad egzistuoja netiesioginis ryšys tarp neautentiškumo santykiuose ir pasitenkinimo gyvenimu, einantis per sudaiktinantį požiūrį į savo kūną.…”
Section: Rezultatų Aptarimasunclassified
“…Based on the OBC theory, overweight women who perceive that they are overweight may have a less positive self concept, lower self-evaluation, and higher insecurity (Bessenoff and Snow 2006;Fredrickson and Roberts 1997;Fredrickson et al 1998;Goldenberg et al 2000;John and Ebbeck 2008;Neighbors et al 2008), and thus they are more likely to cope with body weight-related psychological and health problems by using an avoidance approach (Choma et al 2009). Supporting this notion, previous research has showed that individuals who have a higher level of body shame resulting from the perceived discrepancy between actual self and ideal body self are more likely to experience negative affect and to withdraw from social activities (Anton et al 2000;Fredrickson and Roberts 1997;Fredrickson et al 1998;Heinberg et al 2001;John and Ebbeck 2008;Knauss et al 2008;Mckinley and Hyde 1996).…”
Section: Gender Differences In Body Perceptionmentioning
confidence: 99%
“…On this basis, we suggest that women who have a higher level of perceived body weight may employ avoidance coping strategies, such as withdrawing from work and taking sick leave to evade threats to body image. This may further negatively affect their deteriorated health caused by excessive weight because use of negative coping strategies is associated with poor well-being and psychological distress (Cash et al 2005;Choma et al 2009). Research has shown that people with lower self-esteem, inferior psychological health, or more pessimistic views about their own health are, in fact, more likely to become ill.…”
Section: Gender Differences In Body Perceptionmentioning
confidence: 99%